ESUR guidelines for MR imaging of the sonographically indeterminate adnexal mass: an algorithmic approach - Spencer, John A. (2010)
A significant proportion of adnexal masses detected by sonography are indeterminate. Either their organ of origin is uncertain or it is unclear whether their nature is benign or malignant. MR imaging of the sonographically indeterminate adnexal mass can resolve most of these uncertainties. Most indeterminate masses result from common benign conditions and women with such masses can avoid unnecessary or inappropriate surgery. For the minority of women whose masses are malignant, use of MR imaging rather than a ‘wait and watch’ strategy of repeat ultrasound (US) results in a more timely diagnosis. There are simple diagnostic steps in the MR imaging assessment which direct an algorithmic and problem-solving approach based on signal characteristics and morphology. MR imaging should provide a more timely diagnosis and, thereby, guide the management of the patient with reduced costs of investigation and treatment.